The Effect of Different Doses of Thyroxine Hormone Immersion on Egg Hatchabillity, Growth, and Survival Rate of Larvae (Puntius javanicus Blkr) - Rizka Inanda Harahap; Hamdan Alawi; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT          The study was conducted on 18-30 March 2018, at the Fish Hatchery of Tebing Tinggi, North Sumatera. The purpose of the study was to determine the effect of thyroxine hormone immersion doses on egg hatching rate, larvae growth and survival rate of larvae (Puntiusjavanicus Blkr). The research method was experimental design. the dose of thyroxine hormone solution used was P1 (0 mg / L), P2 (0.05 mg / L), P3 (0.10 mg / L) and P4 (0.15 mg / L) for 24 hours. The results showed that the dose of thyroxine hormone gave a very real effect to egg hatching rate (83,3%) and survival rate (86,67%) of larvae, but did not give significant effect to growth and larvae abnormalitas. The best dose of thyroxine hormone to increase egg hatchability and of larvae growth was 0.15 mg / L and 0.10 mg / L. The water quality parameters during the study were temperature 26-28oC, pH 6.9-7.9; DO 5,4-5, ppm..Keywords:Hatching rate,Thyroxine, Growth, ,larvae.